Exploring visual framing of islam: a comparative analysis - Isyaku, Hassan; Mohd Nazri, Latiff Azmi (2018)
The prevalent image of Islam in the media moved from being presented as quaint to something else. Research shows that analysis of visual elements in the media coverage of Islam is under-represented. This study explores and compares visual framing of Islam in selected Nigerian and Malaysian newspapers. Punch and Vanguard were chosen from Nigeria while The Star and New Straits Times were chosen from Malaysia based on their online readership. The study employed content analysis to analyze 425 photos and 23 videos used in the selected newspapers. Sample was collected from November 2015 until September 2016. Only photos and videos used in articles directly related to Islam were collected from the respective websites of the newspapers. It was found that significant differences exist between Nigerian and Malaysian newspapers in visual framing of Islam. Nigerian newspapers used more violent photos in reporting Islam than Malaysian newspapers. Of all the photos used in the selected newspapers, 43 reflected violence blamed on Islam while 382 were non-violent. None of the videos reflected violence. Though the use of violent photos is minimal in the newspapers, their implication might be highly influential. Visual bias could be avoided through collective effort of journalists, editors, and corporate ownership of the media.